Immunohistochemical analysis of osteopontin expression in oral squamous cell carcinoma - Dhana Lakshmi Jeyasivanesan; Shameena Pazhaningal Mohamed; Deepak Pandiar; Shaini Basheer (Wolters Kluwer Medknow Publications, 2019)
Background: Oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of the oral cavity. Osteopontin (OPN) has been proved as a biomarker in varying malignant tumors. Only limited studies detail the role of OPN in OSCC. Aims: This study aims to demonstrate the expression of OPN in OSCC and to correlate the expression of OPN with the histologic grades of OSCC. Settings and Design: This is a retrospective immunohistochemical study in Dravidian population (linguistically Malayalam). Materials and Methods: Thirty diagnosed cases of OSCC were subjected to immunohistochemistry using OPN antibody for detection of OPN expression. Ten normal oral mucosal specimens were also stained as controls. Statistical Analysis Used: Chi-square test and ANOVA followed by Bonferroni test. Results: OPN expression was significantly higher in OSCC patients than in controls. In normal oral mucosal specimens, none of them showed OPN immunoreactivity. A significant difference was observed between total scores and intensities of normal and varying grades of OSCC. A significant difference was also observed between the percentage of positive cells for OPN expression of normal and varying grades of OSCC. However, no significant difference was observed between the percentage of positive cells for OPN expression of well-, moderate-, poorly-differentiated carcinomas. Correlation of OPN expression with lymph node status, site, and sex was found to be statistically insignificant. Conclusion: Insights gained from this study may lead to research targeted at the treatment of OSCC.